Kajian Teori Kepemimpinan Situasional Dan Kepuasan Kerja : Studi Literature Review - Nabilah Maulidah Az-Zahroh; Cindy Safvitri; Surya Andhika Putra; Mochammad Isa Anshori (Jurnal Riset dan Inovasi Manajemen, 2023)
Job satisfaction of employees is one of the successes for a person who leads an organization. A leader is appointed based on the results of his hard work during his previous work, of course as a leader is appointed because of his work that is considered good and trusted from the organization. Employee job satisfaction can be seen from the leader's treatment of them. The purpose of the study is to analyze whether the situational leadership style affects the job satisfaction of employees in carrying out their duties. By using the literature review study method, data obtained from books and several previous studies. Situational leadership affects job satisfaction. Most employees are more likely to like the situational leadership style because it can make it easier for employees to make work plans for the organization and control employees to prevent unwanted things. Therefore, good leadership in environmental adjustment often leads to job satisfaction.